Prevalence of inflammatory versus neoplastic lesions in dogs with chronic gastrointestinal signs undergoing gastroduodenoscopy: 195 cases (2007–2015). (September 2022) - Ivasovic, F.; Ruetten, M.; Kook, P.H.
Abstract: Objectives: Prevalence of inflammatory enteropathy versus lymphoma in dogs undergoing gastroduodenoscopy has not been evaluated. This retrospective study assessed outcome from 195 client-owned dogs scheduled to undergo upper gastrointestinal endoscopy as the next diagnostic step. Material and methods: Cases were grouped into the following diagnoses according to WSAVA guidelines: lymphoplasmacytic enteritis (LPE), eosinophilic enteritis (EE), mixed-cell enteritis (ME), histologically normal biopsies (N), and lymphoma (L). Clinical signs, and preendoscopic results from laboratory and ultrasonography examinations, were compared among groups. Results: LPE was diagnosed in 133 (68%), EE in 17 (9%), ME in 9 (5%), 32 (16%) dogs had histologically normal biopsies. Four (2%) dogs were diagnosed with lymphoma. Vomiting was the most frequent clinical sign (61%), followed by weight loss (43%), and diarrhea (39%). Vomiting also predominated when looking at individual histological disease categories, however clinical signs did not differ significantly between groups. Dogs with lymphoma were more likely to have ultrasonographic abnormalities, had significantly lower haematocrit, albumin and total protein concentrations compared to dogs with LPE and histologically normal biopsies. Clinical significance: Lymphoma was rarely found in this group of dogs with nonspecific results of pre-endoscopic work-up. Our results provide first reference for clinicians when discussing the possibility of a step-up therapeutic approach (such as multiple dietary trials) with owners before pursuing endoscopy. Understanding the likelihood of finding lymphoma is important in that histologic documentation of inflammatory enteropathy alone has limited therapeutic consequences. Future studies are needed to validate these findings in dogs undergoing combined upper and lower gastrointestinal endoscopy and biopsies. Highlights: Lymphoplasmacytic inflammation predominates in dogs undergoing gastroduodenoscopy. Lymphoma was very rarely (2%) found in duodenal biopsies from dogs worked-up for GI-disease. Understanding the likelihood of finding lymphoma has implications for further case management. Documenting intestinal inflammation alone has limited therapeutic consequences.